Novel pH sensitivity and colorimetry-enhanced anthocyanin indicator films by chondroitin sulfate co-pigmentation for shrimp freshness monitoring - Bao, Yiwen; Cui, Huijun; Tian, Jinlong; Ding, Yumeng; Tian, Qilin; Zhang, Weijia; Wang, Mingshuang; Zang, Zhihuan; Sun, Xiyun; Li, Dongnan; Si, Xu; Li, Bin (Food control, 2022)
A pH-sensitive food freshness indicator film (PS-CS-BA) was fabricated with potato starch (PS) as film-forming substrate, blueberry anthocyanins (BA) as an indicator, and chondroitin sulfate (CS) as an enhancer. The results exhibited that the presence of CS significantly altered water solubility and improved mechanical properties of films, in particular enhanced pH and ammonia responsiveness. FT-IR and XRD results associated with the enhanced pH sensitivity and colorimetry with the ionic complex between the sulfate group of CS and anthocyanin flavylium ion. When applied in monitoring shrimp freshness at 4 °C, the PS–CS–BA film indicated sensitively with vision recognizable color changes from original pink to light grey and finally to grayish-green, which highly correlated with the deterioration indexes of the total volatile basic nitrogen (TVB-N), total viable count (TVC), and pH values of shrimp. The results provided a novel and highly-sensitive intelligent packaging strategy by the co-pigmentation of CS for freshness monitoring. [Display omitted] •PS–CS–BA film was fabricated with starch, chondroitin sulfate and anthocyanins.•Ionic complexes between chondroitin sulfate and anthocyanin produce co-pigmentation.•The addition of chondroitin sulfate enhanced colorimetric and physical properties.•PS–CS–BA film clearly indicated the freshness degree of shrimp during storage.